Syrian hamster (Mesocricetus auratus) as an animal model for Haplorchis taichui infection: biology, morphology, and pathology - Songsri, Jiraporn; Boonmars, Thidarut; Boonjaraspinyo, Sirintip; Aukkanimart, Ratchadawan; Sriraj, Pranee; Boueroy, Parichart; Wongchalee, Nadchanan (The Thai Journal of Veterinary Medicine, 2018)
Haplorchis taichui is a trematode that can mature in the small intestine of mammals and birds, including humans. Larval stages occur in various invertebrate and cold-blooded vertebrate hosts. The purpose of this study was to investigate parasite growth, including worm recovery rate, the body size of adult worms, eggs per worm and eggs per gram of feces and pathological changes of the small intestine in experimental hamsters. In this study, 6- to 8-weekold male Syrian hamsters (Mesocricetus auratus) were each infected with 200 H.taichui metacercariae and then sacrificed at weeks 1, 2, 3, 4, 6 and 8 post-infection. The small intestine and feces of each hamster were collected and processed for analysis.Worm recovery was highest at weeks 1, 2 and 3, then continuously decreased at weeks 4, 6 and 8, respectively. Eggs per worm were highest at weeks 2 and 3, and eggs per gram of feces were highest at week 3. Worm size was similar each week. Histopathological changes in the small intestine were observed, including abnormal villi and goblet cells, as evidenced by short villi and an increase in the number and size of goblet cells, compared with the normal control group.